Penggunaan Al-Qur’an Braille untuk siswa tunanetra di SLB A Negeri 3 Martapura - Dara Puspita Loka; Miffah Khadijah; Ahmad Zaini; Najib Irsyadi (Literal: Disability Studies Journal, 2025)
This study explores the implementation of Braille Qur’an learning for visually impaired students at SLB A Negeri 3 Martapura. Using a qualitative field research approach, the study examines teaching methods, learning processes, and student responses. Data were collected through interviews, observation, and documentation. Data were analyzed used Miles & Huberman stages. Validation of the data involved resources triangulations and member checking. The findings reveal that Qur’anic learning at the elementary level is focused on the introduction of hijaiyah letters using a kinesthetic method, especially through hand gestures representing Braille codes. This method enhances students’ memory and comprehension. Despite challenges such as the complexity of Arabic Braille codes and limited access to digital Braille resources, teachers adopt adaptive strategies like combining Braille reading with audio materials and educational games. These efforts foster an inclusive and engaging learning environment. The study highlights the need for digital Braille Qur’an development and structured teacher training to ensure equitable religious education access for blind students in rural areas.